A study of customers' satisfaction on online banking at Majlis Bandaraya Melaka Bersejarah (MBMB), Melaka / Noorshaeda Sapuan - Sapuan, Noorshaeda (Faculty of Business and Management, 2013)
The history of Majlis Bandaraya Melaka Bersejarah (MBMB) is closely related to Melaka history. Although Melaka has gone through its ups and downs, the city of Melaka has continued to exist. As we know, Majlis .Bandaraya Melaka Bersejarah (MBMB) has larger of organization under government state of Malacca. On 15 April 2003, the historical city of Malacca Municipal Council was upgraded to the Melaka Bandaraya Melaka Bersejarah (MBMB). With this recognition, :rvlBMB will enhance the quality of service to the community in Melaka in particular and general tourists. Progress and prosperity achieved remarkable. Melaka Bandaraya Melaka Bersejarah also known as a local authorities and there are consists 14 departments. The organization provided the services to customer both internal and external. Therefore, the way and procedure works mostly based on online systems. This is easier customers and staffs using the systems to check and updating also made application without any interruption from others. Nowadays, these give advantages of online banking are obvious. The customers can access their personal and business account information while avoiding a trip to the bank (Nor Aini, Za!inawati et. ai, 2012). The implementation of online banking become necessity for every bank to ensure that they are able compete in the global market. The purpose ofthe study is to investigate the customers' satisfaction on online banking at Majlis Bandaraya Melaka Bersejarah (MBMB). The online banking may be measured from demographic profile of staffs as well customer usage. The importance of this study is proposed to give awareness using online bank is the best channel in terms of the way bank operate, deliver and compete, faster and efficiency. Based on analysis of current technology models adopted from Pikkaraine that are proposed factors for online banking system which is there can increasing the satisfaction for the user towards online banking. This paper consists of five chapters which explain the subject matters in stages. Chapter 1 explains the introduction and background of the study, Chapter 2 explains the literature review in which relates to the subject studied and theoretical framework which act as a guide to the research flows and process. For chapter 3, research methodology is explained, which consists of method of sampling technique be used. Data findings and discussion explained in Chapter 4. Lastly, Chapter 5 is containing summary of results and findings which is explain the conclusion and recommendation. It contains six independent variables with the perceive usefulness, ease of use, enjoyment, information of online banking, security and privacy and quality about internet connection, these paper examines how these factors influence the customers' satisfaction on online banking. We designed a questionnaire and used it to survey a simple convenience sampling of staff to collect the data of MBMB. A total of 90 pieces of questionnaire collected from different departments in MBMB. There are having been distributed to the respondents in order to fill out the entire question. From the question the result will be gain after analysis the data. Most of respondents are organization that has used the services from Melaka Bandaraya Melaka Bersejarah (MBMB).